Acute Oxalate Nephropathy in a Young Boy Due to Ingesting Averrhoa Bilimbi; Case Report and Literature Review of an Under-recognized Cause of tropical Renal Disease - Perera, N.R.; Tennekoon, H.D.; Ranawaka, R. (Annals of Pathology and Laboratory Medicine, 2016)
The occurrence of acute oxalate nephropathy (AON) as a result of consuming foods rich in oxalates is well -recognized. Although renal injury has been extensively recognized and described following the ingestion of star fruit (Averrhoa carambola), reports implicating 'bilimbi' (Averrhoa bilimbi), are far less common and were found in adults following ingestion of bilimbi juice. This report describes possibly the first case of AON occurring in an otherwise healthy eight year old boy following the consumption of several bilimbi fruit. Features which favoured dietary hyperoxaluria as the cause for his acute renal injury included the development of acute gastro-intestinal symptoms after ingesting the oxalate rich fruit, the presence of oxalate crystals in the urine full report and renal biopsy and the episodic reversible nature of his illness. Dehydration is likely to have contributed to his AON. The patient was managed medically, did not require dialysis and recovered completely within two weeks. It is important to note that dietary hyperoxaluria causing oxalate nephropathy may be an under-recognised cause of renal disease.
Keywords: acute oxalate nephropathy; Averrhoa bilimbi; dietary hyperoxaluria